LITERATURE REVIEW STUDY ON THE APPLICATION OF SHARIA ACCOUNTING IN MSMES: IMPLEMENTATION AND CHALLENGES - Wulandari, Novita Tri; Mardiana, Mardiana (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to analyze the application of sharia accounting in MSMEs and provide views on the challenges and implementation. This study uses a literature review methodology by collecting several empirical studies related to the application of sharia accounting in MSMEs. The results of this study are to play an important role in the Indonesian economy with its significant contribution to Gross Domestic Product (GDP) and labor absorption. Sharia accounting offers principles of financial management that are transparent, fair, and in accordance with Islamic values. The application of sharia accounting to MSMEs can increase consumer confidence and access to sharia financing. However, the application of sharia accounting in MSMEs is still constrained by a lack of understanding, limited skilled human resources, and a lack of adequate regulatory support and infrastructure. Various efforts need to be made to encourage the adoption of sharia accounting in MSMEs.